One-step preparation of novel conjugated porous polymer with tubular structure - Zhuang Xiaodong; Zhang Yi; Cao Chengan; Zhang Fan; Wu Dongqing; Feng Xinliang (Science China-Chemistry, 2013)
A shape-persistent dendritic molecule, tris(4-(2,7-dibromo-9-phenyl-9- fluoren-9-yl)phenyl)amine (TF-6Br), has been readily synthesized in high yield through a concise Friedel-Crafts reaction from triphenylamine and 2,7-dibromo(9-phenyl-fluoren-9-ol). It was further employed as the key building block to achieve the synthesis of conjugated porous polymer via Sonogashira coupling with 1,4-diethynylbenzene. Under experimental reaction conditions, the resulting porous polymer shows exceptionally nanotubular morphology, which further allows for a template-free synthesis of porous carbon nanotubes via thermal treatment at high temperature. The obtained nitrogen-doped carbon nanotubes feature with an improved porosity and high surface area. © 2013 Science China Press and Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbon nanotube; fluorene; Friedel-Crafts reaction; porous polymer